Board Diversity As Moderator of ESG, Earnings Management, And Risk - Trescova, Cecilia Elsya; Firmansyah, Amrie (Indonesian Journal of Accounting and Governance, 2025)
This study examines the relationship between Environmental, Social, and Governance (ESG) practices and earnings management, considering firm risk and board gender diversity as moderating variables. The phenomenon arises because ESG adoption in Indonesia has skyrocketed, yet its integration into risk management remains questionable. Earnings management is also widely practiced, but its impact on market perceptions of risk remains unclear. Board diversity is often promoted as a governance mechanism, but remains limited in emerging markets. The research utilizes secondary data from 194 non-financial firms listed on the Indonesia Stock Exchange as of 2023. Hypotheses are tested using multiple regression with robust standard errors. The results indicate that ESG and earnings management do not have a significant impact on firm risk, and board gender diversity does not moderate these relationships. These findings indicate that ESG disclosures remain symbolic, earnings management is not perceived as a risk signal, and board diversity has yet to provide adequate oversight. The study suggests the need for more rigorous ESG enforcement, better integration into corporate strategy, and increased female representation on boards.